2016
DOI: 10.1108/rpj-05-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of conductive paths on a fused deposition modeling substrate using inkjet deposition

Abstract: Inkjet deposition is one of the most attractive fabrication techniques for producing cost efficient and lightweight electronic devices on various substrates with low environmental impact. Fused Deposition Modeling (FDM) is one of the most used and reliable additive manufacturing processes by extrusion of wire-shaped thermoplastic materials, which provides an opportunity for embedding printed electronics into mechanical structures during the building process and enables the design of compact smart structures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…[41,42] The advantages of FDM/inkjet hybrid approaches have already been noted for integration of conductive paths. [43][44][45] Both direct-write technologies are already scalable, suitable for fabricating structures with hundreds of layers, and have well-understood formulation and filament/ink requirements. [37][38][39][40]46,47] The work here using standard materials and techniques to fabricate OECTs and to demonstrate neuromorphic behavior demonstrates a clear path for translation to more complex structures and devices that can then progress to applications in bioelectronics.…”
Section: Discussionmentioning
confidence: 99%
“…[41,42] The advantages of FDM/inkjet hybrid approaches have already been noted for integration of conductive paths. [43][44][45] Both direct-write technologies are already scalable, suitable for fabricating structures with hundreds of layers, and have well-understood formulation and filament/ink requirements. [37][38][39][40]46,47] The work here using standard materials and techniques to fabricate OECTs and to demonstrate neuromorphic behavior demonstrates a clear path for translation to more complex structures and devices that can then progress to applications in bioelectronics.…”
Section: Discussionmentioning
confidence: 99%
“…Their studies suggested the irregular surface of the 3D printed substrate led to discontinuity of the inkjet printed pattern and consequently poor conductivity. To improve the continuity of the inkjet printed tracks, they explored two methods: by applying heat and pressure to “iron” the surface and by using a heated metal tip to “plow” a channel to contain the ink (Zhou et al , 2016).…”
Section: Drop Impact Footprint and Resolutionmentioning
confidence: 99%
“…It is highly possible, however, that some of them will gain in commercial interest. Currently, screen printing dominates commercial printed electronics, which can be attributed to its increased use in manufacturing displays and sensors [115,116]. Inkjet printing and high-volume flexography and gravure printing are moving from R&D to pilot and, to some extent, to commercial product manufacturing [115].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%